An Evaluation on Library Cooperation in Türkey - Mehmet E. Küçük; Umut Al; Gülterı Alır; İrem Soydal; Yurdagül Ünal (Türk Kütüphaneciliği)
No library in the world has the sufficient budget, space, and professionals t o ac- cjuire ali existing Information sources, and to organise and serve the acçuired materials. For this reason, libraries cooperate in collection development, cata- loguing, providing access to the others’ collections and document delivery. Aiming at evaluating the co-operation efforts during the Republican erafrom the perspective of the historical, organisational and practicable fields of imple- mentation, this paper examines the library co-operation in Turkey. To determine the present situation, the Turkish National Library, General Directorate of Libraries and Publications, National Academic Network and Information Centr, and some special and school libraries in Ankara, Ministry of National Education, university libraries, consortia, and professional associations are examined, and the data gathered from literatüre and interviews are evaluated. in conclusion, it has been observed that in recent years, co-operation ejfort has gained momentum, two consortia hav e emer ged to provide access to the electronic information sources, document delivery projects between university libraries have been started, but efforts in some practicable fields of co-operation, such as preparing union catalogues, sharing bibliographic data, and develo- ping authority fileş have been unsuccessful. It has also been observed that there is lack of co-operation except among university libraries, and that institutions havefailed in establishing a “common wisdom” and cotısequently in developing the skills of planning and organisation. lnadequacy of resources, legislation, and infrastructure, and most impor- tantly the lack of dedication resulted in discontinuity of the ongoing projects and the production of the new ones.